The Disappointing Performance of Foreign Direct Investment in Industrial Development in Sub-Saharan African Countries - Ojo, Joshua Adewale T.; Adegboye, Folasade Bosede; Olokoyo, Felicia Omowunmi (International Journal of Economics and Financial Issues, 2017)
The Sub-Saharan African region compared to other developing regions has been the most vulnerable as regards foreign capital inflow. The flow of FDI is expected to result into advanced managerial and technological capacities and acceleration of industrial development. The study examined how the flow of FDI to the sub-Saharan African region has impacted the industrial development of the region, using the proxy of industry value added growth. The study made use of pooled data from thirty three sub-Saharan African countries within the period 1993 and 2012.The method of analysis utilized for the study was the fixed effect least-square dummy variable model, employed to estimate the impact of foreign direct investment on industrial development for the selected host countries. The study finds that foreign direct investment is statistically significant in relation to industrial development for host Sub-Saharan African countries; but it is disappointing that the expected desired features of industrial development, like increased manufacturing outputs, reduction in high level of import and manufactured goods; etc, have not been realized. It is therefore recommended that the governments of host countries should put policies in place to encourage development of industries domestically, to enhance sustained industrial development, such that dependence on external financial assistance and borrowing could be reduced, resulting in sustained increases in non-oil export earnings, domestic income, savings, investment, technology, and hence improved living standard. Keywords: Foreign Direct Investment; Industrial Development; Sub-Saharan African Countries JEL Classifications: F21, O14